HLA inherence as a potential parameter in checkpoint inhibitor-associated autoimmune adverse event assessment - Gandarillas, Sophia; Newland, Elizabeth Schoenberg; Toppmeyer, Deborah; Stephenson, Ryan; Denzin, Lisa; Dasgeb, Bahar (Frontiers in Medicine, 2024)
Background The success of immunotherapy has made it a lifesaving treatment, but not without side effects. Currently, the risk factors for developing immune-related adverse events (irAEs) in patients who receive immunotherapy are poorly understood, and there is no risk-stratifying mechanism for potentially fatal irAEs. It is postulated that oncology patients with preexisting autoimmune diseases are likely to have flares on immunotherapy. However, some patients develop de novo autoimmune conditions on immunotherapy without a prior history. Literature reports have postulated that human leukocyte antigen (HLA) inherence may play a role in irAEs. However, this potential remains underexplored. Methods The oncology patients who developed autoimmune adverse events on immunotherapy for whom the continuation of treatment was prudent or lifesaving were selected. Of note, all nine patients received checkpoint inhibitors (CIs). Of the nine selected patients, only one had a prior history of an autoimmune condition. None of the nine selected patients had an active autoimmune condition at the time of CI initiation. Their HLA was typed, and the results were cross-referenced with the literature reports in PubMed and Google search with the corresponding autoimmune condition of each patient. Results Herein, we report nine patients with irAEs for whom retrospective HLA typing revealed the inherence of multiple related HLA alleles that may correspond to the autoimmune condition that they had developed on immunotherapy. It is to be mentioned that the inherence of enriched disease-related HLA alleles was shared among patients with the same irAEs. These patients developed a range of irAEs including bullous pemphigoid, pemphigus foliaceus/vulgaris, thyroiditis, vitiligo, and hepatitis on immunotherapy. Although some combinations of disease-related HLA were well reported in otherwise idiopathic autoimmune diseases, a frequently repeated HLA allele combination in our patient population was found to be rarely seen in the general population. Conclusion The authors suggest that an enriched inherence of disease-related HLA alleles may play a role in the genetic propensity for the development of irAEs in oncology patients, who receive immunotherapy, including CIs. Inherence of more than one or a cluster of particular autoimmune disease-related HLA alleles in patients who receive immunotherapy may unmask the corresponding autoimmune disease as the genotype inherence presents with the phenotype of the corresponding condition. It is suggested that enriched linked HLA genotypes, which are otherwise rare in the general population, may present as the corresponding phenotype of the autoimmune condition. Such clinical presentation, enhanced by immunotherapy, such as CIs, can play a role in risk stratifying patients for precision medicine and improve the outcome.